THE ROLE OF RIFTING IN THE EVOLUTION OF THE CONTINENTAL MARGIN OF EASTERN ASIA: GEOPHYSICAL EVIDENCE - Rodnikov A.G.; Rodnikova R.D.; Zorina Y.G. (My University, 1992)
The role of rift processes is analysed in the structural evolution of the continental margins of Eastern Asia including the Indo-China Peninsula and North China plain. Paleoreconstructions were made for the Indo-China Peninsula to characterize individual stages of rifting covering the Late Cretaceous-Eocene, Oligocene-Middle Miocene and Late Pliocene-Early Quaternary epochs. The rifting of continental margins occurred synchronously with spreading processes in marginal seas, whereas the formation of rift structures in the North China plain was concurrent with the formation of a deep-water basin of the Philippine Sea. The development of asthenospheric diapire led to crustal extension and was responsible for the formation of rift structures in marginal seas and continental margins.
Keywords: Quaternary; Pliocene; Cretaceous; Eocene; Miocene; Oligocene; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Eocene; Кайнозой::Неоген::Миоцен; Cenozoic::Neogene::Miocene; Кайнозой::Палеоген::Олигоцен; Cenozoic::Paleogene::Oligocene; Мезозой::Меловая; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Четвертичная; Cenozoic::Quaternary; Mesozoic::Cretaceous